Students Perspicacity Concerning Faculty’s teaching Performance of Shanker Dev Campus - Parajuli, Suman Kamal; Kandel, Deepak Raj (International Research Journal of MMC, 2023)
Faculty members are considered the most precious assets in any educational institution, and their interactions with students are critical to curriculum achievement, so this study focuses on assessing Shanker Dev Campus students' perspicacity on faculty performance. The study was survey in nature and used objectivity methods to explain the data. Structure questionnaire was used to collect data. The participants in this research were graduate students enrolled in the Master of Business Studies and Master of Business Management programmers. The reliability was examined using Cronbach's alpha, and a value of 0.86 was found. Findings show that faculty expertise on topics seems strong, students and faculty have a close relationship in the class, and faculty encouraged students to do well in their studies and profession. The SDC faculty strictly adhered to the timetable. However, students felt their teachers rarely utilized worksheets, article journals, management games, and real-world examples. Moreover, the faculty shortly planned different activities in order to keep class busy. There were no significant associations between female and male students’ perspicuity of faculty knowledge on the subject matter, encouragement to create a learning environment, supportive relationships/motivation, and time spent in class. This study emphasized the importance of faculty development, pedagogical innovation, curriculum enhancement, teacher-student interaction, and continuous improvement in enhancing the teaching performance at Shanker Dev Campus.